2017
DOI: 10.1186/s12903-017-0446-6
|View full text |Cite
|
Sign up to set email alerts
|

Dental and medical health status and oral health knowledge among visually impaired and sighted female schoolchildren in Riyadh: a comparative study

Abstract: BackgroundThe impact of visual impairment on oral health in the literature is inconclusive, and the available information on the medical and dental health status of visually impaired children is limited. The aim of this study was to evaluate the dental and medical health status, and to assess the oral health knowledge of visually impaired girls aged 6–12 years, and compare them to that of sighted children.MethodsThis analytical cross-sectional study was carried out on 79 visually impaired and 83 age-matched si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(67 citation statements)
references
References 18 publications
6
58
0
3
Order By: Relevance
“…Our sample was summed up in 148 males and 119 female individuals from different primary and middle schools (aged [6][7][8][9][10][11][12][13][14][15] in Riyadh, Saudi Arabia. The sample were given the questionnaire and interviewed following the WHO oral health assessment form for children.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our sample was summed up in 148 males and 119 female individuals from different primary and middle schools (aged [6][7][8][9][10][11][12][13][14][15] in Riyadh, Saudi Arabia. The sample were given the questionnaire and interviewed following the WHO oral health assessment form for children.…”
Section: Resultsmentioning
confidence: 99%
“…Factors such as poor OHI scores, higher PI scores, and higher GI scores were observed among the visually impaired children compared with the sighted group. 14…”
Section: Introductionmentioning
confidence: 99%
“…Children participated in this study were pre-screened on the computer system for eligibility, and parents were contacted by phone to assign an appointment. On the intervention day, the primary caregiver parent was asked to complete two questionnaires fully along signing a consent form; one questionnaire was regarding demographic data which was translated from English into Arabic and was validated and utilized in a previous study [17]. Minor modifications were added to the demographic questionnaire to suit the study objectives.…”
Section: Methodsmentioning
confidence: 99%
“…They cannot visualize visible dental caries or whether gingival bleeding exists during tooth brushing, which consequently affects their oral health status and early dental visit [ 4 ]. In previous studies, poor oral hygiene [ 5 7 ], and gingival bleeding [ 5 , 8 11 ] were frequently observed in visually impaired children. High prevalence of dental caries [ 5 ], and frequent trauma to the anterior teeth were also reported for these children [ 7 , 8 , 12 ].…”
Section: Introductionmentioning
confidence: 99%